FUNGSI BADAN PERMUSYAWARATAN DESA PADA ASPEK PENGAWASAN UNTUK MENINGKATKAN KINERJA KEPALA DESA DI DESA TAKULAT KECAMATAN KELUA KABUPATEN TABALONG - Suparti, Heni (Jurnal PubBis, 2021)
Based on the Peraturan Menteri Dalam Negeri Number 110, the Village Consultative Body has the function of supervising the performance of the Village Head, the supervision as intended is carried out through planning, implementing and reporting on the administration of village governance. In carrying out the supervisory function of the Village Consultative Body on the planning, implementation and reporting of village administration, it is intended as a preventive effort so that the village government in carrying out village government does not make deviations. This study aims to determine the function of the village consultative body in the aspect of supervision to improve village heads. This study used descriptive qualitative method. Data collection techniques used in-depth interviews, with data validity using data triangulation. The data analysis technique uses an interactive model through the stages: data condensation, data presentation, and drawing conclusions. The results showed that the function of the village consultative body in the aspect of supervision to improve the performance of the Village Head in Takulat Village, Kelua District, Tabalong Regency had been implemented "quite well".